2019
DOI: 10.1186/s12913-019-4610-3
|View full text |Cite
|
Sign up to set email alerts
|

Preference and uptake of different community-based HIV testing service delivery models among female sex workers along Malaba-Kampala highway, Uganda, 2017

Abstract: IntroductionFemale Sex workers (FSW) and their clients accounted for 18% of the new HIV infections in 2015/2016. Special community-based HIV testing service delivery models (static facilities, outreaches, and peer to peer mechanism) were designed in 2012 under the Most At Risk Populations Frame work and implemented to increase access and utilization of HIV care services for key populations like female sex workers. However, to date there is no study that has been done to access the preference and uptake of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 2 publications
3
38
0
Order By: Relevance
“…Three cross sectional studies also reported HIV testing as an outcome (34,37,40). In a study conducted in…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Three cross sectional studies also reported HIV testing as an outcome (34,37,40). In a study conducted in…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…HIV diagnosis was measured in six cross-sectional studies (27,28,32,34,37,38), two randomized controlled trials (25,35) and one quasi-experimental study (39). The quasi-experimental study (Fig.…”
Section: Hiv Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…However, no published data are available on STI and HIV testing practices among HMSW in Uganda. Despite paucity of data on STI testing practices, up to 86% of FSW in Uganda report taking an HIV test in the prior 12 months [29,30]. Our study aimed to assess and compare recent HIV and syphilis screening practices among HMSW, relative to FSW, in selected urban centers in Uganda.…”
Section: Introductionmentioning
confidence: 99%